2023
DOI: 10.1186/s40662-023-00336-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual and patient-reported outcomes of a diffractive trifocal intraocular lens in highly myopic eyes: a prospective multicenter study

Abstract: Background To investigate the visual and patient-reported outcomes of a diffractive trifocal intraocular lens (IOL) in highly myopic eyes. Methods Patients with planned cataract removal by phacoemulsification and implantation of a trifocal IOL (AT LISA tri 839MP) were enrolled in the prospective, multicenter cohort study. Patients were allocated into three groups according to their axial length (AL): control group, AL < 26 mm; high myopia group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…An prospective cohort study, Sun et al [26] observed that there were no significant differences in the coma aberration, spherical aberration and trefoil aberration among eyes with different ALs, and the proportion of trefoil aberration was also larger than other aberrations from 0.23 μm to 0.25 μm. While Meng et al [27] found there was the greater intraocular HOAs and coma aberration in the extreme myopia group (AL>28 mm). As for whether CTRs can reduce internal HOAs is still controversial.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringsmentioning
confidence: 82%
“…An prospective cohort study, Sun et al [26] observed that there were no significant differences in the coma aberration, spherical aberration and trefoil aberration among eyes with different ALs, and the proportion of trefoil aberration was also larger than other aberrations from 0.23 μm to 0.25 μm. While Meng et al [27] found there was the greater intraocular HOAs and coma aberration in the extreme myopia group (AL>28 mm). As for whether CTRs can reduce internal HOAs is still controversial.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringsmentioning
confidence: 82%